2001
DOI: 10.1016/s0020-1693(01)00425-x
|View full text |Cite
|
Sign up to set email alerts
|

Copper complexes with bibracchial lariat ethers: from mono- to binuclear structures

Abstract: Copper(II) complexes with a series of bibracchial lariat ethers are described. Independently of the nature of the counterion present (nitrate or perchlorate), the lariat ether N, N%-bis(2-aminobenzyl)-1,10-diaza-15-crown-5 (L 1 ) always forms mononuclear complexes, whereas the lariat ethers N, N%-bis(2-aminobenzyl)-4,13-diaza-18-crown-6 (L 2 ) and N,N%-bis(2-salicylaldiminobenzyl)-4,13-diaza-18-crown-6 (L 3 ) only give binuclear compounds. The X-ray crystal structure of [CuL 1 ](ClO 4 ) 2 shows a seven-coord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…We have carried out studies to asses their different complexation capabilities towards post-transitional divalent metal ions such as Zn(II) [17], Pb(II) and Cd(II) [18][19][20][21] as well as transition metal ions. With first-row transition metal ions such as Ni(II), Co(II) and Cu(II), L 2 and L 4 are able to form binuclear complexes [22,23], whereas the related receptors L 1 and L 3 only form mononuclear complexes [24][25][26]. Interestingly, these mononuclear complexes represent unusual examples of structurally characterized seven coordinate (pentagonal bipyramidal) complexes of first-row transition metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…We have carried out studies to asses their different complexation capabilities towards post-transitional divalent metal ions such as Zn(II) [17], Pb(II) and Cd(II) [18][19][20][21] as well as transition metal ions. With first-row transition metal ions such as Ni(II), Co(II) and Cu(II), L 2 and L 4 are able to form binuclear complexes [22,23], whereas the related receptors L 1 and L 3 only form mononuclear complexes [24][25][26]. Interestingly, these mononuclear complexes represent unusual examples of structurally characterized seven coordinate (pentagonal bipyramidal) complexes of first-row transition metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…The Zn II ion behaves in a different way, and addition of chloride anions to the Zn II perchlorate in the presence of L 4 does not lead to the formation of a binuclear complex. The formation of these binuclear systems was followed by spectrophotometric ti- We recently demonstrated that the pendant-armed crown ethers N,NЈ-bis(2-aminobenzyl)-1-10-diaza-15-crown-5 (L 1 , Scheme 1) [5,6] and N,NЈ-bis(benzimidazol-2-yl-methyl)-1,10-diaza-15-crown-5 (L 3 ) [7] form mononuclear complexes in acetonitrile solution with divalent first-row transition-metal ions that represent unusual examples of structurally characterized seven-coordinate (pentagonal bipyramidal) complexes. [8] Particularly interesting are also the coordinative properties towards these divalent metal ions of the larger related receptor N,NЈ-bis (2-aminobenzyl with the metal ions being five-or six-coordinate, [9] whereas the corresponding mononuclear complexes could not be isolated.…”
Section: Introductionmentioning
confidence: 99%
“…The few examples of X-ray structure of the [15]crown-5-Cu 2+ systems found in the literature led us to present here the partially resolved structure of [Cu(L2)] 2+ (Figure 2). [6,10,12,20] 2+ in solution, which is different from the asymmetric structure found in the solid state.…”
Section: Structure Of [Cu(l2)](clo 4 )mentioning
confidence: 57%
“…The [15]crown-5-based ligands usually lead to heptacoordinated complexes with metal ions, the most common polyhedron being the pentagonal bipyramid [19] with either O 7 , [11,12] N 2 O 5 , [10,20] or N 4 O 3 [6,8,9,14] coordination spheres. The pentagonal equatorial plane is probably imposed by the rigid structure of the [15]crown-5 ligand.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation